Determination of Calculation for the Shape of Blades Trace in the Concrete Mixer Truck. (2015) - Fedorko, Gabriel; Kral, Jan; Kral, Jan; Ristovic, Ivica; Molnar, Vieroslav
Abstract: The article deals with a calculation of parameters of blades track for a concrete mixer truck, according to which the blades are placed inside a conical drum in the direction of the helix and are welded then. The issue dealt with is important for accurate determination of the shape of the blades traces according to which the shape of the shanks is drawn inside the drum and the blades are welded after their application inside the drum. The correct shape of the blades track and positioning of the blades in the direction of the helix, as well as the correct welding all affect the concrete consistency during its transport to the final destination. For automated calculation, a mathematical analysis based on theoretical review of the issue is provided in the article. The analysis is done with the use of differential geometry which is optimal for this issue. The results are summarized in a flowchart and the calculation itself is done in the programming environment of Turbo Pascal.